Strategies for improving serological and molecular detection of plant pathogenic bacteria - López, María M.; Llop, Pablo; Cubero, Jaime; Penyalver, Ramón; Caruso, Paola; Bertolini, Edson; Penyalver, Javier; Gorris, María T.; Cambra, Mariano (2017)
Serological and molecular techniques are the most appropriate for rapid detection of plant pathogenic bacteria in plant material. They can reach high specificity when selected probes are used and high sensitivity after optimisation of the most important steps of each technique. ELISA and PCR are techniques widely used for developing simple protocols useful for processing large number of samples in routine. As they are based in different principles and probes, their combination allows accurate, rapid and specific detection of the bacteria in plant material. Several aspects of their optimisation for detecting some phytopathogenic bacteria are described here.